COMMUNITY EMPOWERMENT EFFORTS THROUGH CREATIVE ECONOMY AR THE BUBAH BEAUTY COURSE AND TRAINING INSTITUTE (LKP) BANJARWORO BANGILAN VILLAGE - Muhammad Yusuf Aminuddin; Inarotul A'yun; Irma Rosyidah; Siti Halimus Sunnah (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2022)
Community empowerment is a process of developing community potential with the aim that people can be independent in overcoming problems that are often experienced. The combination with community creativity is expected to have a positive impact on the economic progresss of the community. The purpose of this study is to describe community empowerment efforts through the creative economy in achieving capacity development, independence, empowerment, and community productivity. This type of research includes descriptive research with a qualitative approach, using primary and secondary data sources. Data collection techniques through interviews, observation and documentation as a complement preformance obtain information data. The results showed that community empowerment efforts through the creative economy carried out by LKP Bubah Beauty in assisting the improvement of community welfare were carried out with a development framework (enabling), stengthening potential and power (empowering) and creating idependence.